Regulation of expression, activity and localization of fungal chitin synthases - Rogg, Luise E. (2011)
The fungal cell wall represents an attractive target for pharmacologic inhibition, as many of the components are fungal-specific. Though targeted inhibition of β-glucan synthesis is effective treatment for certain fungal infections, the ability of the cell wall to dynamically compensate via the cell wall integrity pathway may limit overall efficacy. To date, chitin synthesis inhibitors have not been successfully deployed in the clinical setting. Fungal chitin synthesis is a complex and highly regulated process. Regulation of chitin synthesis occurs on multiple levels, thus targeting of these regulatory pathways may represent an exciting alternative approach. A variety of signaling pathways have been implicated in chitin synthase regulation, at both transcriptional and post-transcriptional levels. Recent research suggests that localization of chitin synthases likely represents a major regulatory mechanism. However, much of the regulatory machinery is not necessarily shared among different chitin synthases. Thus, an in depth understanding of the precise roles of each protein in cell wall maintenance and repair will be essential to identifying the most likely therapeutic targets.